PENGARUH LEVERAGE, FIRM SIZE, DAN FINANCIAL DISTRESS TERHADAP AKTIVITAS HEDGING PADA SUB SEKTOR LEMBAGA PEMBIAYAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Fitriani, Asri Rizki; Khairunnisa, Khairunnisa (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2020)
The development of investment activities is currently developing rapidly and becomes routine activities carried out by the company. The company makes investments to get profits in the future, the business development that is undertaken, and the management of its capital. Investment activities need to pay attention to the existence of sources of risk, one of which is the risk of currency exchange rates and interest rate risk. One risk mitigation is carried out to minimize investment risk in the company by hedging. The purpose of this study is to find and analyze the variables that are suspected to influence hedging activities, namely leverage, firm size, and financial distress. This study uses logistic regression analysis and descriptive statistics which are processed using SPSS 25. This study takes the object of a sub-sector of financial institutions listed on the Indonesia Stock Exchange in the 2014-2018 period. The samples in this study are 15 companies using purposive sampling techniques. The result in this study is firm size significantly influence hedging activity. Then, leverage and financial distress does not affect hedging activities.